Molecular picture of cobalamin C/D defects before and after newborn screening era. (March 2017) - Nogueira, C; Marcão, A; Rocha, H; Sousa, C; Fonseca, H; Valongo, C; Vilarinho, L
Objective: Birth prevalence of Cobalamin (Cbl) C or D defects in Portugal is an estimated 1:85, 000, one of the highest worldwide. We compared the genotype/phenotype of patients identified with CblC or CblD before and after the implementation of expanded newborn screening. Methods: Twenty-five Portuguese CblC/D patients, 14 symptomatic and 11 identified through screening, were diagnosed using gas chromatography or tandem mass spectrometry. Molecular characterization was performed through the study of MMACHC and MMADHC genes. Results: The most common MMACHC mutation, c.271dupA, was present in 100% of MMACHC alleles of all CblC screened patients, in contrast with the 61% identified before expanded newborn screening. All studied cases (except one, who presented a CblD deficiency) presented a CblC defect. More CblC late-onset patients were diagnosed before the introduction of newborn screening than in the post newborn screening era, probably because some early onset patients died without a definitive diagnosis. Conclusion: The molecular data found in this cohort contribute to the improvement of screening and diagnosis of Cbl defects and would enable a confirmatory diagnosis of these patients, reducing the need for complex, costly, laborious, and time-consuming biochemical/enzymatic tests.